Physical activity and gait kinematics in the elderly - Victor Pitzer Neto; Airton Rombaldi; Mirelle Saes; Fernando Siqueira (Revista Brasileira de Atividade Física e Saúde)
The paper proposed to analyze the gait kinematics of different physical activity levels. A cross-sectional study, with 60 seniors, divided according to level of physical activity into groups of active, insufficiently active and inactive seniors. The kinematic parameters investigated in gait were stride length, gait speed, distance between the ground and the hallux and the angles of the hip, knee and ankle. Kinovea 0.8 and ImageJ were used for photogrammetric data analysis and STATA 9.2 was used for statistical analysis. Average stride length, gait speed and distance between the hallux and the ground were significantly higher among physically active seniors. As for the ankle joint angle, during the gait phase referred to as toe-off, the angle was greater in the active group (82.98, SD 5.96) compared with the inactive group (86.05, SD 5.44) (p=0.025). Average knee joint angles in degrees during the toe-off phase were 151.02 (SD 10.03) in the active group, 151.12 (SD 7.79) in the insufficiently active and 143.35 (SD 7.08) (p= 0.006) in inactive group. In the acceleration phase the results were 126.81 (SD 7.26), 123.81 (6.60) and 130.4 (6.94) in each group (p=0.015), respectively. Our findings demonstrated that physical activity is important to reduce changes to gait caused by the natural aging process. Physical activity should therefore be widely encouraged among the elderly as a preventive and health promotion in measure this population.